2014
DOI: 10.1111/bjdp.12078
|View full text |Cite
|
Sign up to set email alerts
|

Conforming to coordinate: Children use majority information for peer coordination

Abstract: Humans are constantly required to coordinate their behaviour with others. As this often relies on everyone's convergence on the same strategy (e.g., driving on the left side of the road), a common solution is to conform to majority behaviour. In this study, we presented 5-year-old children with a coordination problem: To retrieve some rewards, they had to choose the same of four options as a peer partner--in reality a stooge--whose decision they were unable to see. Before making a choice, they watched a video … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Therefore, here we add a new type of information that children can use to solve the knowledge problem in coordination problems. Previous studies have shown that 5-year-old children are able to solve different coordination problems by using salience (Grüeneisen, Communicative eye contact signals a commitment 32 Wyman, & Tomasello, 2015a), majority information (Grüeneisen, Wyman, & Tomasello, 2015b), and their partners' cultural knowledge (Goldvicht-Bacon & Diesendruck, 2016). Study 1 extends these findings by focusing on interpersonal signals that children can use in solving coordination problems.…”
Section: Discussionmentioning
confidence: 68%
“…Therefore, here we add a new type of information that children can use to solve the knowledge problem in coordination problems. Previous studies have shown that 5-year-old children are able to solve different coordination problems by using salience (Grüeneisen, Communicative eye contact signals a commitment 32 Wyman, & Tomasello, 2015a), majority information (Grüeneisen, Wyman, & Tomasello, 2015b), and their partners' cultural knowledge (Goldvicht-Bacon & Diesendruck, 2016). Study 1 extends these findings by focusing on interpersonal signals that children can use in solving coordination problems.…”
Section: Discussionmentioning
confidence: 68%
“…Indeed, a striking aspect of coordination in humans is that people often manage to jointly agree on a solution even without communicating (Mehta, Starmer, & Sugden, 1994; Schelling, 1960). Recent studies have shown that some of these abilities are already present in late preschoolers (Goldvicht-Bacon & Diesendruck, 2016; Grueneisen et al, 2015a, 2015b, 2015c). However, whether children can also coordinate without communication when facing conflicts—for example, when having to tacitly agree on a division of resources—would be an interesting question for future research.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has shown that already at age 5 children show first competencies at coordinating decisions even in one‐shot interactions in which they cannot communicate. For example, they can coordinate on solutions they jointly perceive to stick out, either because the solution is perceptually salient (Grueneisen et al, 2015a), others have coordinated on the solution previously (Berger et al, 2021; Grueneisen et al, 2015b), or because the solution can be presumed to be known by members of their cultural community (Goldvicht‐Bacon & Diesendruck, 2016). To achieve this, children often make fairly sophisticated inferences about their interaction partner's perceptual states or beliefs and align their own decisions accordingly (Grueneisen et al, 2015c; Siposova et al, 2018).…”
Section: Discussionmentioning
confidence: 99%